Analysis of the Reduction in the Duration of Sick Leave for 32,512 Psoriasis Patients Following the Integration of Targeted Therapies for Psoriatic Disease into the Brazilian Healthcare System: a Retrospective Cohort Study - D'Almeida LFV; Duarte GV; Godinho MP; Cariello LH; Sousa GJB; Gomes CM (Psoriasis: Targets and Therapy)
Luiza Ferreira Vieira D’Almeida,1,2 Gleison Vieira Duarte,3 Marcos Paulo Godinho,2 Louise Habka Cariello,1 George Jó Bezerra Sousa,4 Ciro Martins Gomes1,5 1Programa de Pós-Graduação em Ciências Médicas da Faculdade de Medicina, Universidade de Brasília, Brasília, Distrito Federal, Brazil; 2Dermatology Department, Instituto de Dermatologia Do Prof. Rubem David Azulay, Rio de Janeiro, Brazil; 3Dermatology Department, Instituto Bahiano de Imunoterapia, Salvador, Bahia, Brazil; 4General Coordination of Surveillance of Leprosy and Diseases in Elimination of the Department of Transmitted Diseases, Ministry of Health, Brasília, Distrito Federal, Brazil; 5Programa de Pós-Graduação em Patologia Molecular da Faculdade de Medicina, Universidade de Brasília, Brasília, Distrito Federal, BrazilCorrespondence: Ciro Martins Gomes, Faculdade de Medicina, Campus Universitário Darcy Ribeiro - Asa Norte, Brasília, 70910-900, Brazil, Email cirogomes@unb.brPurpose: The Brazilian Unified Health System is an interesting model for international healthcare innovation analysis. Covering over 200 million people, this system stands out as one of the largest purchasers of healthcare technologies worldwide. Our goal in this study was to evaluate how targeted therapies reduce the duration of sick leave for psoriasis patients.Patients and Methods: We conducted a retrospective cohort study within the Brazilian National Institute of Social Security. The primary outcome was the return to work (cessation of sick leave) of patients with psoriasis. Factors such as age, sex, and access to targeted therapies were evaluated using a Cox proportional hazards model.Results: Over the 25-year period from 1998 to 2023, 32,512 benefits were granted for psoriasis, totalling an expenditure of $577,478,002.15. Public access to psoriatic arthritis (PsA)-targeted therapies decreased the average minimum wage granted to psoriasis patients on sick leave by 22%, and public access to psoriasis-targeted therapies reduced the average wage by 7%. The availability of these therapies was associated with earlier cessation of sick leave in our proportional hazards model (targeted therapies for PsA: hazard ratio (HR) = 1.90, 95% confidence interval (CI) = 1.82– 2.00; targeted therapies for psoriasis: HR = 1.63, 95% CI = 1.54– 1.70).Conclusion: This study highlights a remarkable reduction in costs and sick leave duration due to the implementation of therapies for psoriatic disease by the Brazilian Unified Health System, which underscores the importance of considering detailed indirect cost data when evaluating new health technologies for large populations.Plain Language Summary: Psoriasis is a chronic inflammatory disease affecting more than 60 million people worldwide. The disease is known to affect genetically predisposed individuals after an environmental trigger, sparking a relentless cycle of skin and systemic inflammation. The Brazilian Unified Health System offers an interesting case study for analysing the financial implications of cutting-edge healthcare technologies. Serving over 200 million diverse individuals, it is one of the world’s largest single buyers of healthcare technologies. In the CLEAR and FIXTURE trials, compared with ustekinumab and etanercept, secukinumab not only demonstrated superior efficacy but also significantly reduced work impairment for patients and the associated indirect costs of psoriasis from weeks 16 through 52 in the United Kingdom. Although controlled clinical trials have illustrated the positive impacts of effective therapies for psoriasis, there is a considerable gap in real-world data. Our study examines the impact of targeted therapies on reducing the duration of sick leave for psoriasis patients, leveraging extensive big data analysis from the Brazilian National Institute of Social Security system. Our findings revealed a significant reduction in costs and sick leave durations owing to the implementation of these therapies for psoriatic disease. This study underscores a remarkable reduction in costs and sick leave duration due to the implementation of therapies for psoriatic disease by the Brazilian Unified Health System. This finding highlights the importance of considering detailed indirect cost data when evaluating new health technologies for large populations.Keywords: psoriasis, arthritis, psoriatic, costs and cost analysis, health care costs, health expenditures